Pengaruh Penerapan Model Pembelajaran Konstruktivisme terhadap Hasil belajar Siswa dalam Pembelajaran Menggambar Teknik di SMA Negeri 1 Lengayang - YONI INDRIATI, Ir. Drs. Heldi, M.Si, Yasrul Sami, S.Sn, M.Sn (Universitas Negeri Padang, 2013)
The purpose of this research is to find out: the influence of the application of the learning model of kontruktivisme on experimental classes (XI IPA2) with conventional learning on grade control (XI IPA 3) toward student learning outcomes in learning drawing techniques in SMA Negeri 1 Lengayang. This type of research is research conducted experiments. The population of this research is the grade XI IPA SMA Negeri 1 Lengayang. Selected Class experiment (XI IPA2) and control classes (XI IPA3). Research results can reveal there is the influence of the application of the learning model of kontruktivisme on experimental classes (XI IPA2) which can give better results of Conventional Learning Class (XI IPA 3) in Learning drawing techniques in class XI IPA SMA Negeri 1 Lengayang. It can be seen from the significant level data processing results of α = 0.05 thitung value ttabel value and 1,976 1,680. If thitung > ttabel. Kata kunci : Model Kontruktivisme, Hasil Belajar, Menggambar teknik